The Linguistical Interpretation of Xavier’s Sarcastic Memes in 9GAG - Azizah, Putri Rahma Aulia; Farani, Yasmin; Kusumowati, Dewi (British (Jurnal Bahasa dan Sastra Inggris), 2024)
As a part of linguistics, figurative language is always interesting to study since it is used in daily life as well. For example, it is applied in literary works (i.e., poetry) and music (i.e., songs). The aims of this study are, first, to analyze the use of figurative language in Xavier’s memes and, second, to interpret their meaning. In this study, the researchers chose one of the branches of figurative language, which is called irony, and merely focused on sarcasm as the verbal type of irony. As this is mostly qualitative research, the researchers do library research, including online browsing. This anonymous person called Xavier is often featured in memes, pictures, and videos uploaded by a lot of people at the 9gag platform, a social media website allowing users to upload and share user-generated content, including memes, funny pictures, and videos. It happens that Xavier is popular for his sarcastic comment memes uploaded to 9gag, and they mostly roast or mock others’ content in funny ways. The finding shows that most of Xavier's sarcastic comment memes use propositional, like-prefixed, and lexical sarcasm; for example, (1) Like Tiktokers"—like-prefixed sarcasm and (2) First man to win an argument against a woman"—lexical sarcasm.